Biomechanics research and sport equipment development - Stefanyshyn, D. J.; Wannop, J. W. (Sports Engineering, 2015)
Advances in sport equipment have revolutionized athletic competition with engineers developing equipment that can enhance performance. However, not all athletes are able to benefit from the new, ideal equipment, with some athletes performing worse. Although the engineering may be sound, the interaction between the piece of equipment, the athlete, and the action is missing. The purely mechanical system of the piece of equipment becomes a biomechanical system once it is interacting with the athlete. Research into the underlying mechanisms of performance in sport has relied heavily on biomechanical studies. The review of these studies has identified important performance and injury variables that can be influenced by sport equipment. This baseline information helps provide a fundamental understanding of human performance that guide equipment designers and developers. A flawlessly engineered mechanical piece of sport equipment can still fail if the athlete-equipment interaction is not properly addressed in the design process. How an athlete uses a piece of equipment and furthermore how an athlete may change or adapt to changes in properties of a piece of equipment must be taken into consideration. Using properties of footwear as an example, research has provided understanding of the biomechanical limiting factors regarding the influence of footwear traction on athletic performance. Data on other footwear properties such as cushioning and forefoot bending stiffness are limited. Intrinsic musculoskeletal properties, such as the force-length and force-velocity relationships of skeletal muscle, can be exploited through equipment design, as has been shown during cycling. Modifications to equipment parameters can shift the operating range of an athlete within these relationships to maximize force or power output, which was shown during the development of the clap skate. Additionally, these properties vary slightly from athlete to athlete and minor adjustments to a piece of sporting equipment can help optimize individual athletes according to their specific biomechanical characteristics.